Menggugah Nilai Lokal Melalui Gerak: Integrasi Permainan Tradisional dalam Koreografi Pendidikan Anak : Menggugah Nilai Lokal Melalui Gerak: Integrasi Permainan Tradisional dalam Koreografi Pendidikan Anak - Titis Sefi Andhini; Rika Mellyaning Khoiriya (STKIP Subang, 2026)
The choreography of “Sangkan Paraning Dolanan” is a traditional dance that incorporates Javanese children's games such as Cublak-Cublak Suweng, Engklek, and Ular Naga as a medium for teaching character to elementary school students. Through a descriptive choreography analysis approach, this work shows how the simple movements of traditional games can convey the values of honesty, sportsmanship, unity, and mutual cooperation. The integration of regional songs and local cultural elements reinforces the relevance of enjoyable, meaningful, and child-appropriate arts education. As a result, this dance is not only an artistic expression, but also a means of cultural preservation and character building based on direct experience.